Close, yet so far away: a phenomenology of the praecox feeling in the diagnosis of schizophrenia as intercorporeal alienness - Vial, Iván; Moskalewicz, Marcin; Szuła, Anastazja; Schwartz, Michael A.; Fuchs, Thomas (Frontiers in psychiatry, 2024)
Debates concerning the reliability and validity of operationalized criteria and diagnostic tools have surrounded the issue of schizophrenia diagnosis and clinical decision-making related to the disorder. The notion of the praecox feeling (PF) has played a prominent role in the discussions as an example of the possibility of a rapid and potentially valid diagnosis based solely on “intuition” or a peculiar emotional experience or impression arising in a physician during an interaction with a patient with schizophrenia. In this paper, we argue that PF is enabled by the (phenomenologically understood) intercorporeal dimension of the clinical encounter. Intercorporeality in this sense denotes intertwinement between embodied expressions that may lead to feelings of connection but also, as in the case of PF, of disconnection and strangeness—the experience of alienness. Following Waldenfels, alienness ranges from the average social encounter to more extreme and peculiar forms—such as PF. To prove our point, we analyze the metaphors used by physicians in various cultural contexts (the United States, the United Kingdom, and Poland) to express the apparently ineffable experience of the PF. We focus on two dominant metaphors of distance: the first expressing spatial distance by referring to an “object in-between” the physician and the patient and the second expressing mental distance by referring to the “other-worldliness” of the patient. We interpret the object in-between metaphors as reflecting the sense of separateness and the other-worldliness metaphors as reflecting the sense of strangeness, with both meanings unified in the notion of “close remoteness.” Such unsettling but speculation-provoking feeling of close remoteness may be rendered by the concept of “the eerie” (Mark Fisher). We conclude that metaphor and phenomenological analysis facilitate an understanding of the experiential profile of PF in the clinical encounter, outlining relevant clinical implications.
Gesehen am 21.11.2024